Analysis The Effect of Minds-On Activity on The Computational Thinking Ability of Early Childhood Student - Jebpridar Nikma Fadhila; Cucuk Wawan Budiyanto; Rosihan Ari Yuana (Journal of Informatics and Vocational Education, 2022)
CT (Computational Thinking) involves solving problems, forming systems, and understanding human behavior by drawing basic concepts to science, CT is also included as a thinking tool that reflects the breadth of the field of computer science. This generation familiarity with technology helps to form a solid background for understanding the key to underlying concepts of computing. Hands-on activity and Minds-on activity refer to active learning which means that a person combines physical activity with mental activity in terms of learning. Hands-on activities and Minds-on activities are most effective when used to focus and encourage students to be physically involved while learning. When students are physically and mentally engaged, they activate the different parts of their brain. The research method used is a qualitative method.